Effect of microplatelet orientation in 3D printed microplatelet reinforced composites with bioinspired microstructures - Peng, Weixiang (2024)
Complex microstructures are the hallmark of natural ceramic biocomposites, but limited processing methods to reproduce them hinder the understanding of mineral orientation roles on the mechanical properties. This study investigates the influence of microplatelet orientation in composite materials, utilizing the magnetically assisted direct ink writing method (M-DIW) to create microstructured microplatelet-reinforced composites. Experimental and computational approaches are employed to explore the critical role of microplatelet orientation on the flexural properties of these materials. Horizontal microplatelets are found to significantly enhance the composite's flexural toughness by promoting overlap and increasing fracture energy during crack propagation. Vertical microplatelets contribute to increased flexural modulus and strength. Perpendicular microplatelets facilitate straight crack paths and smoother fracture surfaces. Moreover, complex microstructural designs were introduced by strategically combining microplatelet orientations to optimize mechanical properties. These findings emphasize the vital role of microplatelet orientation in composite materials, offering potential for tailored materials with superior performance.